Cytomorphology of Chimeric Antigen Receptor T-Cells (CAR-T) - Eugenio Galli; Silvia Bellesi; Marcello Viscovo; Federica Sorà; Stefan Hohaus; Nicola Piccirillo; Luca Laurenti; Patrizia Chiusolo; Valerio De Stefano; Simona Sica; Gina Zini (Mediterranean Journal of Hematology and Infectious Diseases)
Chimeric antigen receptor (CAR) T cells represent one of the newest frontiers of cell therapy. Their application currently involves relapsed/refractory aggressive B cell lymphoma and leukemia as a standard of care, while several studies are exploring CAR-T to treat multiple myeloma and other hematological malignancies. Here we describe the cytomorphology of CAR-T collected from the leftovers of infusion bags, and therefore before the encounter with the antigen, with, among others, a peculiar population of giant lymphoid cells with blastoid features and hypertrophic centrosome.